MAKNA TRADISI HAJAT BUMI DI DESA BLENDUNG, PURWADADI, SUBANG, JAWA BARAT TAHUN 2015-2019 - Herawati, Novi (KARMAWIBANGGA: Historical Studies Journal, 2021)
This study aims to determine: (1) The origin of the Hajat Bumi Tradition in Blendung Village, Purwadadi District, Subang Regency. (2) The procession of implementing the Hajat Bumi Tradition in Blendung Village, Purwadadi District, Subang Regency. (3) Meaning of Hajat Bumi Tradition in Blendung Village, Purwadadi District, Subang Regency. The method used in this research is a qualitative research method with a descriptive approach. In this study, there are two types of data and data sources, namely primary data, data through direct interviews and secondary data, data in the form of journals and books. Data collection techniques used are observation, in-depth interviews, documentation. The data analysis techniques used were data collection, data reduction, data presentation, conclusion and verification. Techniques for checking the validity of the data used were source triangulation and theory triangulation. The results of this study indicate that: (1) The origin of the tradition of hajat the earth has been carried out since the time of our ancestors. (2) The procession of carrying out the tradition of hajat the earth starts from the formation of a committee, saving and carrying out a series of tawasul events, traveling around the village, thanksgiving and entertainment. (3) The tradition of hajat the earth was originally interpreted as an expression of gratitude and an arena to strengthen ties. With the development of the times, the interests of the earth have shifted in terms of meaning. Nowadays it is interpreted as a means of community entertainment, preserving culture and a means of socializing agricultural extension.